Estudo da captura e sequestro de carbono aplicados na indústria de petróleo e gás natural - Facio, Vitor de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The mineral carbonation is considered one of the Carbon Capture and Sequestration technologies, which will allow the continued use of fossil fuels, such as oil and natural gas. This is a world-researched area, but in Brazil there is still a lack of information about it, as it is a relatively new area in this country. In this graduation work it was performed an experimental study of the mineral carbonation, evaluating the potential of using the Brazilian serpentinite as raw material in this process. For it, the serpentine was properly prepared and characterized in order to ensure that this was a good choice. After, acidic dissolution tests were performed using hydrochloric acid, in order to extract the serpentine elements such as magnesium. The wastes obtained in this process were evaluated using thermal analysis techniques in order to compare the thermal behavior of the waste to that of the material as it came from nature. Finally, preliminary tests were performed on mineral carbonation

A carbonatação mineral é tida como uma das tecnologias de Captura e Sequestro de Carbono que permitirá o uso continuado dos combustíveis fósseis, tais como petróleo e gás natural. Esta é uma área pesquisada mundialmente, mas que no Brasil ainda há um déficit de informações a respeito, sendo uma área relativamente nova em território nacional. Neste Trabalho de Graduação (TG) foi realizado um estudo experimental da carbonatação mineral, avaliando o potencial da utilização do serpentinito brasileiro como matéria neste processo. Para tal, o serpentinito foi devidamente preparado e caracterizado, de modo a garantir que esta era uma matéria promissora. Em seguida foram realizados ensaios de dissolução ácida utilizando ácido clorídrico, de modo a extrair do serpentinito elementos como o magnésio. Em seguida, após os resíduos obtidos deste processo foram avaliados utilizando técnicas de análise térmica, de modo a averiguar os constituintes e o comportamento dos resíduos quando comparados com o material in natura. Por fim foram realizados ensaios preliminares de carbonatação mineral
Keywords: Seqüestro de carbono; Combustiveis fosseis; Rochas igneas; Carbon sequestration